Factors associated with plasma antigen carbohydrate 125 and amino-terminal pro-B-type natriuretic peptide concentrations in acute heart failure. Issue 5 (1st August 2020) - Miñana, Gema; de la Espriella, Rafael; Mollar, Anna; Santas, Enrique; Núñez, Eduardo; Valero, Ernesto; Bodí, Vicent; Chorro, Francisco J; Fernández-Cisnal, Agustin; Martí-Cervera, Jorge; Sanchis, Juan; Bayés-Genís, Antoni; et al.
Abstract : Background: Plasma amino-terminal pro-B-type natriuretic peptide and antigen carbohydrate 125 levels are positively associated with a higher risk of adverse clinical outcomes in acute heart failure. As a proxy of congestion, antigen carbohydrate 125 has also been proposed as a right-sided heart failure marker. Thus, we aimed to determine in this population the main factors – including echocardiographic right-sided heart failure parameters – associated with antigen carbohydrate 125 and amino-terminal pro-B-type natriuretic peptide. Methods and results: We prospectively included 2949 patients admitted with acute heart failure. Amino-terminal pro-B-type natriuretic peptide and antigen carbohydrate 125 were used as dependent variables in a multivariable linear regression analysis. The mean age of the sample was 73.9±11.1 years; 48.9% were female, 35.8% showed ischaemic aetiology, and 51.6% exhibited heart failure with preserved ejection fraction. The median (interquartile range) for amino-terminal pro-B-type natriuretic peptide and antigen carbohydrate 125 were 4840 (2111–9204) pg/ml and 58 (26–129) U/ml, respectively. In a multivariable setting, and ranked in order of importance (R 2 ), estimated glomerular filtration rate (43.7%), left ventricle ejection fraction (15.1%), age (12.4%) and high-sensitivity troponin T (10.9%) emerged as the most important factors associated with amino-terminal pro-B-type natriuretic peptide. The five main factors associated with antigen carbohydrate 125 were, in order of importance: the presence of pleural effusion (36.8%), tricuspid regurgitation severity (25.1%), age (11.9%), amino-terminal pro-B-type natriuretic peptide (6.5%) and peripheral oedema (4.3%). Conclusion: In patients with acute heart failure the main factors associated with amino-terminal pro-B-type natriuretic peptide were renal dysfunction, left ventricle ejection fraction and age. For antigen carbohydrate 125, clinical parameters of congestion and the severity of tricuspid regurgitation were the most important predictors. These results endorse the value of antigen carbohydrate 125 as a useful marker of right-sided heart failure.